SOSIALISASI PEMELIHARAAN JARINGAN IRIGASI BAGI PETANI PEMAKAI AIR DESA UNRA KECAMATAN AWANGPONE KABUPATEN BONE - Rizky Apriati Azis; Christy Agata Makupiola; Mariati Indah Lestari; Jumiati Bandu (Journal of Excellence Humanities and Religiosity, 2026)
To empower irrigation networks to achieve optimal performance, intensive, consistent, and targeted maintenance is essential. This targeted maintenance is essential. This community service program aimed to educate farmers on irrigation network maintenance in Unra Village, Bone Regency. The method used was a face-to-face lecture with a lecturer from the Faculty of Engineering and Agriculture. The outreach program ran smoothly and effectively